A framework for improving the effectiveness of evidence-based practices in vocational rehabilitation. - Kydd, Rob; Lockett, Helen; Waghorn, Geoffrey (Journal of Vocational Rehabilitation, 2018)
BACKGROUND: Vocational rehabilitation for people with severe mental illnesses has reached a critical stage in its development of evidence-based practices. A recent meta-analysis has suggested that good program quality measured by fidelity scales is necessary but not sufficient to achieve good employment outcomes. It is likely therefore that there are other aspects of program implementation quality that are not addressed by the current scales. OBJECTIVE: The aim of this study was to identify new dimensions of program quality potentially applicable to improving the effectiveness of evidence-based vocational rehabilitation. METHODS: A review and synthesis of the theoretical and empirical literature in the broader science of psycho-social program implementation was conducted to identify the core dimensions which could be applied to evidence-based vocational rehabilitation. RESULTS: Twenty reviews and four single studies identified the common dimensions of a generic implementation framework. Empirical findings from eight of these, and 19 additional papers built a conceptual framework for improving evidence-based practices in vocational rehabilitation. The resulting framework consists of nine dimensions of implementation quality and twenty-three contextual factors. CONCLUSIONS: This conceptual framework will assist program funders, researchers, practitioners, and policymakers to consider a wider range of program influences to advance the science and practice of vocational rehabilitation for people with severe mental illness.